Corporate socially responsible investing in Sub-Saharan Africa: A factor of shareholders’ value creation? - OUSMANOU , Alim (Revue Internationale des Sciences de Gestion, 2024)
This study analyses the impact of corporate socially responsible investing on corporate shareholder value creation in Sub-Saharan Africa. The sample includes 12 companies from 8 Sub-Saharan African countries that meet two criteria: (i) operating in a sector (agriculture) with a significant impact on the environment, and (ii) publishing full financial and sustainability reports from 2010 to 2022. The information used was obtained from secondary data collected between 2010 and 2022. These data were analysed through a time cross-sectional regression corrected for any latent heteroscedasticity and serial autocorrelation. The findings indicate that average rate of socially responsible investing is 7% turnover compared to 60% turnover of classical investment, and the average rate of shareholder value creation is 65% equity. However, the study finds that socially responsible investments do not significantly impact shareholder value creation. Therefore, the study concludes that socially responsible investment is not a source of shareholder value creation for companies in Sub-Saharan Africa.